2016
DOI: 10.3389/fpsyg.2016.01700
|View full text |Cite
|
Sign up to set email alerts
|

Interference among the Processing of Facial Emotion, Face Race, and Face Gender

Abstract: People can process multiple dimensions of facial properties simultaneously. Facial processing models are based on the processing of facial properties. The current study examined the processing of facial emotion, face race, and face gender using categorization tasks. The same set of Chinese, White and Black faces, each posing a neutral, happy or angry expression, was used in three experiments. Facial emotion interacted with face race in all the tasks. The interaction of face race and face gender was found in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…These studies all found that the race and the sex of the faces influenced emotion recognition. Studies by Craig and Lipp (2018) and Li and Tse (2016) found the largest happy advantage for own-race female faces. Smith et al (2017), found an anger advantage for other-race Black male faces (but not White male faces or female faces) and the largest happy advantage for other-race (Black) female faces.…”
Section: Interactions Between Emotional Expression and Sex 16mentioning
confidence: 89%
See 1 more Smart Citation
“…These studies all found that the race and the sex of the faces influenced emotion recognition. Studies by Craig and Lipp (2018) and Li and Tse (2016) found the largest happy advantage for own-race female faces. Smith et al (2017), found an anger advantage for other-race Black male faces (but not White male faces or female faces) and the largest happy advantage for other-race (Black) female faces.…”
Section: Interactions Between Emotional Expression and Sex 16mentioning
confidence: 89%
“…When faces vary by sex and emotion as well as an additional social dimension (e.g., race, attractiveness), the influence of sex on emotion recognition also becomes less consistent. For example, a number of studies have asked participants to categorize faces varying in race, sex, and emotional expression (Craig & Lipp, 2018;Li & Tse, 2016;Smith et al, 2017). These studies all found that the race and the sex of the faces influenced emotion recognition.…”
Section: Interactions Between Emotional Expression and Sex 16mentioning
confidence: 99%
“…More broadly, future investigations could also consider the impact of task-irrelevant emotional expressions on categorization of gender or ethnicity in faces as a means to understanding potential preferential processing of positive emotion information in older adults. Evidence suggests multiple facial features are processed when only one particular feature is explicitly attended to ( Mouchetant-Rostaing et al, 2000 ; Ito and Urland, 2005 ; Ambron et al, 2016 ; Li and Tse, 2016 ). For example, recent work by Li and Tse (2016) with young participants showed that task-irrelevant emotional expressions in target faces interacted with the processing of gender or race when the faces were categorized on the latter dimensions, and Ambron et al, 2016 found that when gender in a distractor face was used to cue the non-face target to be reached for, task-irrelevant facial expression modulated the degree to which reaching paths deviated to the distractor faces.…”
Section: Discussionmentioning
confidence: 99%
“…Further, faces depicting Black women were rated as less attractive than White women, an effect that was mediated by ratings of masculinity. Numerous studies in face-based judgments have since expanded these findings by varying the racialization of the stimuli ( Johnson et al, 2012 ; Hopper et al, 2014 ), the study’s target population, and age of participants being studied ( Kim et al, 2015 ; Li and Tse, 2016 ; Lei et al, 2020 ). Importantly, the results of Goff et al clearly expose a research bias toward white women in sex/gender-related social cognition research, based on a white majority (82%) of participants, as well as the erasure of Black women exemplified in Stolier et al’s face stimuli visualization (2017), see Figure 1 .…”
Section: Research Theme #2: How Individuals Process Intersecting Social Identitiesmentioning
confidence: 99%